Panic Disorder Induced by the Coronavirus Disease Pandemic in a Patient with Organic Mood Disorder Successfully Treated with Vortioxetine - Yoshimura, Reiji; Okamoto, Naomichi; Konishi, Yuki; Ikenouchi, Atsuko (Case Reports in Psychiatry, 2020)
We present a case of panic disorder induced by the coronavirus disease (COVID-19) pandemic in a patient with an organic mood disorder. The patient was a 62-year-old woman with mild mood swings and reduced motivation and volition caused by a traumatic brain injury after a traffic accident. She was maintained on carbamazepine (600 mg/day). When the COVID-19 outbreak occurred in Japan, she developed concerns regarding the illness and complained of multiple episodes of panic attacks. Further, her depressive symptoms worsened. Thus, vortioxetine was added to the ongoing CBZ treatment. Four weeks after initiating vortioxetine treatment, the symptoms of panic disorder and depressive state were ameliorated. The present case suggests that vortioxetine augmentation can improve symptoms of depressive state and panic disorder induced by the COVID-19 pandemic.